Improvement of technological-mathematical model for the medium-term prediction of the work of a gas condensate field - Kutia, Mykhailo; Fyk, M. I.; Kravchenko, Oleg; Palis, Stefan; Fyk, I. (Технологический Центр, 2016)
Authors proposed analytical and algorithmic additions to the mathematical model of the prediction of the work of a gascondensate field in the gas regime. The developed technique of improved calculations of the gasdynamic parameters was verified by the actual history of a number of real fields in Ukraine. It demonstrated good results by accuracy in the course of mediumterm prediction, which is important for estimating the efficiency of the measures for the intensification of well production. The new analytical construction of the systems of equations of the planeradial inflow of gas to the well bottom and transport of gas by the vertical column allowed us to make the algorithm of iterative calculations more universal. The universality consists, in particular, in the possibility to predict the results of thermobaric changes in the gas flow and changes in the design parameters of a well after technological measures for the intensification of well production. The unique difference is the possibility of rapid evaluation of the prediction of intensification of a well with the interference into both the productive layer and the downhole equipment. Authors emphasized the need for a similar further improvement of the technologicalmathematical model taking into account the new technologies of intensification, including innovative technological schemes of constructing the downhole equipment, equipment for the column of wells, wellhead equipment, multibottom and multirow systems of extraction, extraction of gas with injection into the layer of special chemical agents. The certain properties of the adaption correction of parameters made it possible to use the program realization of the developed technologicalmathematical model at the UkrainianSwedish gasextraction company TOV "Karpatygaz".

Предложены аналитические и алгоритмические дополнения к математической модели прогноза работы газоконденсатного месторождения в газовом режиме. Усовершенствована методика расчетов прогнозов основных газодинамических параметров продуктивных залежей. Для проверки новой модели использовались данные месторождений Украины. Созданная программная реализация разработанной технолого-математической модели внедрена и апробирована в газодобывающем производстве.
Совершенствование технолого-математической модели среднесрочного прогноза работы газоконденсатного месторождения
Keywords: gascondensate field; intensification of inflow; Gasfield development indicators; mathematical model; gasdynamic calculation; газоконденсатное месторождение; интенсификация притока; добыча углеводородов; показатели разработки месторождения; газодинамический расчет